2010
DOI: 10.1073/pnas.0912115107
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for solute transport, nucleotide regulation, and immunological recognition of Neisseria meningitidis PorB

Abstract: PorB is the second most prevalent outer membrane protein in Neisseria meningitidis. PorB is required for neisserial pathogenesis and can elicit a Toll-like receptor mediated host immune response. Here, the x-ray crystal structure of PorB has been determined to 2.3 Å resolution. Structural analysis and cocrystallization studies identify three putative solute translocation pathways through the channel pore: One pathway transports anions nonselectively, one transports cations nonselectively, and one facilitates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(116 citation statements)
references
References 63 publications
3
110
0
Order By: Relevance
“…For example, Im and Roux (44) found that the electrostatic interactions between ions and the charge distribution of the OmpF channel play an important role in governing ion permeation and selectivity. An additional example of this type of pore feature that may support dPNAG translocation is the electropositive extracellular surface features of PorB from pathogenic Neisseria meningitides may mediate Toll-like receptor recognition through a nonspecific electrostatic attraction (45,46). In our structure, the PgaA barrel pore is closed on the extracellular surface by several loops, whereas the PgaA barrel is fully open on the periplasmic side, with a dimension of ϳ25 Å ϫ 35 Å in diameter.…”
Section: Discussionmentioning
confidence: 83%
“…For example, Im and Roux (44) found that the electrostatic interactions between ions and the charge distribution of the OmpF channel play an important role in governing ion permeation and selectivity. An additional example of this type of pore feature that may support dPNAG translocation is the electropositive extracellular surface features of PorB from pathogenic Neisseria meningitides may mediate Toll-like receptor recognition through a nonspecific electrostatic attraction (45,46). In our structure, the PgaA barrel pore is closed on the extracellular surface by several loops, whereas the PgaA barrel is fully open on the periplasmic side, with a dimension of ϳ25 Å ϫ 35 Å in diameter.…”
Section: Discussionmentioning
confidence: 83%
“…PorB is a TLR2 agonist that activates cells via a TLR2/TLR1-dependent signaling pathway (22)(23)(24). Recently, it has been hypothesized that the interaction between PorB and TLR2 occurs through a ring of positively charged residues on the porin's surface-exposed regions and opposing negatively charged residues on the TLR2 ectodomain (43). However, PorB proteins from different Neisseria strains possess regions of high amino acid sequence variability, concentrated in the surface-exposed loops (8).…”
mentioning
confidence: 99%
“…Nevertheless, our data support PorA behavior as a potential oral adjuvant. PorB has been extensively studied at the structural and functional levels, 76 and its mechanism as an adjuvant involves TLR2/TLR1 hybrid recognition 77 and enhancing cell survival and continued activation through mitochondrial interactions, protecting these cells from apoptosis. 78 We compared the resistances of PorA and PorB against known gastrointestinal proteases and observed that PorA performed better than PorB when both porins were submitted to proteolytic degradation.…”
Section: Resultsmentioning
confidence: 99%